Comparative Preclinical Evaluation of the Tumor-Targeting Properties of Radioiodine and Technetium-Labeled Designed Ankyrin Repeat Proteins for Imaging of Epidermal Growth Factor Receptor Expression in Malignant Tumors; International Journal of Molecular Sciences; Vol. 26, iss. 21 - Larkina M. S. Mariya Sergeevna; Yanovich G. Gleb; Hasnowo L. A. Lutfi Aditya (Hasnowo Lutfi Aditya; Varvashenya R. N. Ruslan Nikolaevich; Yuldasheva F. Sh. Feruza Sherzod kizi; Tretyakova (Tretjyakova) M. S. Maria Sergeevna; Plotnikov E. V. Evgeny Vladimirovich; Zelchan (Zeltchan) R. V. Roman Vladimirovich; Shulga (Schulga) A. A. Aleksey Anatolievich; Konovalova E. V. Elena Valerjevna; Ziganshin R. Rustam; Belousov M. V. Mikhail Valerievich; et al. (2025, 2025)
Title screen